Photocatalytic Hydrogen Evolution: Interfacial Engineering for Improved Photocatalysis in a Charge Storing 2D Carbon Nitride: Melamine Functionalized Poly(heptazine imide) (Adv. Energy Mater. 6/2021). Issue 6 (11th February 2021) - Kröger, Julia; Jiménez‐Solano, Alberto; Savasci, Gökcen; Rovó, Petra; Moudrakovski, Igor; Küster, Kathrin; Schlomberg, Hendrik; Vignolo‐González, Hugo A.; Duppel, Viola; Grunenberg, Lars; Dayan, Cem B.; Sitti, Metin; et al.
Abstract : In article number 2003016, Bettina V. Lotsch and co‐workers demonstrate that covalent surface modifications of the 2D carbon nitride poly(heptazine imide) with melamine groups strongly influence its polarity and photo(electrochemical) properties. This potent tuning pathway also results in the boosting of photocatalytic hydrogen evolution due to increased donor interactions and enhanced hole extraction.